Unsafe Sexual Practices and Associated Factors Among Female Sex Workers in Sagamu Local Government, Ogun State, Nigeria (African Journal of Biomedical Research, 2022)
One of the public health challenges that have gripped the universe is the rapid spread of the Human Immunodeficiency Virus. Unprotected heterosexual intercourse remains central to HIV transmission in Nigeria, as in most of sub-Saharan Africa and female sex workers play a crucial role in the spread of the virus through unsafe sex practices. Globally, sex workers make up 9% of the total number of new HIV infections and while HIV prevalence among the population in Nigeria has been declining from its peak of 5.8% in 2001 to 1.4% in 2018, prevalence among sex workers remains high at 14.4%%  A descriptive cross-sectional study of 81 Female Sex Workers out of the estimated total population of 360 FSWs based in brothels only, in Sagamu local government was selected. The majority 63(77.8%) of the respondents engaged in unsafe sex practices. The majority 65(80.3%) had a low to moderate risk perception of STI/HIV/AIDs. Almost half participants 36(44.4%) had the erroneous belief that they could not contract HIV. Statistically significant association was found between unsafe sexual practices and previous history of STIs among FSWs (p = 0.021), reported current HIV status (p = 0.019), alcohol use (p = 0.004), and binge alcohol (p = 0.037). Unsafe sex practice is highly prevalent among female sex workers in Sagamu with low to moderate risk perception for HIV/AIDs / STI.
Keywords: female sex workers; HIV/AIDS; Perception; Unsafe sexual practices; brothel based; sexually transmitted infections